The level of understanding of zakat on savings among workers at Perbadanan Kemajuan Iktisad Negeri Kelantan (PKINK) / Nur Amni Syuhada Azhan - Azhan, Nur Amni Syuhada (2024)
This paper aimed to identify the Level of Understanding of Zakat on Savings Among Workers At Perbadanan Kemajuan Iktisad Negeri Kelantan (PKINK). The level of understanding of Zakat on savings is a question of the level of understanding of workers at PKINK about the basics of Zakat on savings and its relationship with knowledge, religiosity, and attitudes. In this research study, the main sampling method being used by the researcher is non-probability sampling. The researcher used a non-probability sampling of the people who work in PKINK, regardless of their position and rank. A sample size is 100 respondents was chosen to obtain the data. In this study, the data was analyzed by using statistical software known as Statistical Package for Social Science (SPSS). This researcher uses frequency analysis, reliability analysis, regression analysis, and Pearson correlation analysis to analyze the data. In this study, the results show that knowledge, religiosity, and attitudes have a significant influence on the workers at PKINK in payment Zakat on savings.